Manajemen Sumber Daya Manusia dalam Meningkatkan Motivasi dan Suasana Religius di MI GUPPI At-taqwa Ketosari Kecamatan Bener Kabupaten Purworejo - ., Yakino; Nurlailiyah, Siti (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2021)
This research is based on the importance of human resource management in a madrasa. In connection with this, this research aims to determine Human Resource Management in Increasing Motivation and Religious Atmosphere at MI GUPPI AT-TAQWA Ketosari, Bener District, Purworejo Regency. This research is qualitative research. Data collection uses interviews, observation, and documentation, and data validity uses triangulation, and data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. This research produces five conclusions: (1) The use of human resources to increase motivation and religious atmosphere at MI Guppi At-Taqwa, Ketosari Village, Bener District, Purworejo Regency has not been optimal. In recruiting educational personnel, they still use simple methods and still use old methods. (2) Human resource selection to improve motivation and religious atmosphere at MI Guppi At-Taqwa, Ketosari Village, Bener District, Purworejo Regency is carried out through: Preliminary acceptance of applicants, acceptance tests, selection interviews, reference checks and medical evaluations, interviews with direct superiors, and Acceptance decision. (3) Human resource development to improve motivation and religious atmosphere at MI Guppi At-Taqwa, Ketosari Village, Bener District, Purworejo Regency, is carried out by holding training and coaching to continuously learn and develop the madrasa's personal competencies. Apart from that, it is also through: Job performance assessment, guidance and counseling, disciplinary development, and training. (4) Maintaining human resources in improving motivation and religious atmosphere at MI Guppi At-Taqwa, Ketosari Village, Bener District, Purworejo Regency is carried out through several things, including: providing compensation, employee service, security and safety. The madrasah pays attention to all this in order to maintain good working relationships. (5) The use of human resources in increasing motivation and religious atmosphere at MI Guppi At-Taqwa, Ketosari Village, Bener District, Purworejo Regency, including: Career planning and job expansion. Apart from that, we also provide the widest possible opportunities for employees to develop various careers to achieve their plans to be more advanced and able to compete in the future.